Effects of Paroxetine, Bupropion and Agomelatine on Reproduction Hormones and Sperm Parameters in Male Rats - Bulmus, Ozgur; Yardimci, Ahmet; Ulker, Nazife; Ozdemir, Gokcen; Ozcan, Mete; Canpolat, Sinan; Kelestimur, Haluk (Wiley, 2015)
[Abstract Not Available]